The question of the efficiency of the workflow of loop propellers - A. V. Mesropyan; Yu. A. Shabelnik (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
The purpose of the work is to find ways to improve the characteristics of water propellers. Taking into account that propellers are the most widely used, considered one of the possible promising schemes - a loop-shaped propeller, which makes it possible to significantly improve the hydrodynamic, acoustic, vibration and cavitation characteristics of the propeller. The work uses numerical simulation, on the basis of which the propeller action curves are calculated to identify the influence of geometric parameters of the loop propeller on its working process. A comparison of various variants of loop propellers is carried out, identified the most perspective combination of geometric parameters. The requirements for the propulsors of perspective ships set the task of increasing the efficiency of propellers, which are solved by parametric optimization of the geometry of non-traditional schematic solutions of propellers.